Blue Resilience - Peerzadi Hossain, Rumana; Kondowe, Jonah; Mudege, Netsayi; Dhulipala, Ram (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This is a presentation made during the launch of the digital climate advisory tool for aquaculture known as Blue Resilience.